2021
DOI: 10.3389/fnagi.2021.695117
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Loss and Dementia: A Meta-Analysis of Prospective Cohort Studies

Abstract: Background: Consensus is lacking with regard to whether hearing loss is an independent risk factor for dementia. We therefore conducted a meta-analysis to clarify the relationship of hearing loss and dementia.Methods: Prospective cohort studies investigating the association between hearing loss and the incidence of dementia in a community-derived population were included by searching electronic databases that included PubMed, Embase, and Cochrane's Library. A random-effects model was adopted to combine the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 42 publications
2
43
0
Order By: Relevance
“…Attenuating these risk factors could potentially play a role in reducing the ADRD burden in the US. We provide estimates of the individual population-attributable risks (PARs; ie, the proportion of cases of a disease in a population that may be attributed to a given risk factor) for each of the 7 modifiable risk factors originally studied as well as hearing loss, selected because of growing evidence of its association with ADRDs and the combined PAR (accounting for nonindependence between factors) for the US overall and by sex and racial and ethnic subpopulations.…”
Section: Introductionmentioning
confidence: 99%
“…Attenuating these risk factors could potentially play a role in reducing the ADRD burden in the US. We provide estimates of the individual population-attributable risks (PARs; ie, the proportion of cases of a disease in a population that may be attributed to a given risk factor) for each of the 7 modifiable risk factors originally studied as well as hearing loss, selected because of growing evidence of its association with ADRDs and the combined PAR (accounting for nonindependence between factors) for the US overall and by sex and racial and ethnic subpopulations.…”
Section: Introductionmentioning
confidence: 99%
“…Self‐reported hearing impairment was associated not only with dementia but also with accelerated multidomain cognitive decline and cognitive impairment 21 . Moreover, a recent meta‐analysis demonstrated that hearing loss was independently associated with a higher incidence of Alzheimer's disease 22 . Our findings indicate that strategies to mitigate the negative impacts of hearing impairment might benefit all individuals studied.…”
Section: Discussionmentioning
confidence: 59%
“…Based on this, CiteSpace was used to identify burst keywords, and it seems that “mechanism,” “association,” “dementia,” “risk,” and “decline” have been the strongest burst keyword since 2017. A large number of studies have found that the hearing loss predated and predicted a subsequent clinical diagnosis of dementia ( Thomson et al, 2017 ; Zheng et al, 2017 ; Loughrey et al, 2018 ; Liang et al, 2021 ). Dementia or cognitive decline is a devastating disease and global health challenge that is highly prevalent worldwide.…”
Section: Discussionmentioning
confidence: 99%